MicroRNAs in Vitis vinifera cv. Chardonnay Are Differentially Expressed in Response to Diaporthe Species - Eichmeier, Ales; Kiss, Tomas; Penazova, Eliska; Pecenka, Jakub; Berraf-Tebbal, Akila; Baranek, Miroslav; Pokluda, Robert; Cechova, Jana; Gramaje, David; Grzebelus, Dariusz (Genes, 2019)
Diaporthe species are important pathogens, saprobes, and endophytes on grapevines. Several species are known, either as agents of pre- or post-harvest infections, as causal agents of many relevant diseases, including swelling arm, trunk cankers, leaf spots, root and fruit rots, wilts, and cane bleaching. A growing body of evidence exists that a class of small non-coding endogenous RNAs, known as microRNAs (miRNAs), play an important role in post-transcriptional gene regulation, during plant development and responses to biotic and abiotic stresses. In this study, we explored differentially expressed miRNAs in response to Diaporthe eres and Diaporthe bohemiae infection in Vitis vinifera cv. Chardonnay under in vitro conditions. We used computational methods to predict putative miRNA targets in order to explore the involvement of possible pathogen response pathways. We identified 136 known and 41 new miRNA sequence variants, likely generated through post-transcriptional modifications. In the Diaporthe eres treatment, 61 known and 17 new miRNAs were identified while in the Diaporthe bohemiae treatment, 101 known and 21 new miRNAs were revealed. Our results contribute to further understanding the role miRNAs play during plant pathogenesis, which is possibly crucial in understanding disease symptom development in grapevines infected by D. eres and D. bohemiae.
Keywords: RT-qPCR; MicroRNAs; Ascomycota; transkriptom; high-throughput sequencing; grapevine; Transcriptome; Vitis; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; mikro RNA; miRNA